Pathologic correlates of supranuclear gaze palsy with parkinsonism. (May 2017) - Martin, W.R.W.; Hartlein, J.; Racette, B.A.; Cairns, N.; Perlmutter, J.S.
Abstract: Introduction: Supranuclear gaze palsy (SGP) is a classic clinical feature of progressive supranuclear palsy (PSP) but is not specific for this diagnosis and has been reported to occur in several other neurodegenerative parkinsonian conditions. Our objective was to evaluate the association between SGP and autopsy-proven diagnoses in a large population of patients with parkinsonism referred to a tertiary movement disorders clinic. Methods: We reviewed clinical and autopsy data maintained in an electronic medical record from all patients seen in the Movement Disorders Clinic at Washington University, St. Louis between 1996 and 2015. All patients with parkinsonism from this population who had subsequent autopsy confirmation of diagnosis underwent further analysis. Results: 221 unique parkinsonian patients had autopsy-proven diagnoses, 27 of whom had SGP documented at some point during their illness. Major diagnoses associated with SGP were: PSP (9 patients), Parkinson disease (PD) (10 patients), multiple system atrophy (2 patients), corticobasal degeneration (2 patients), Creutzfeld-Jakob disease (1 patient) and Huntington disease (1 patient). In none of the diagnostic groups was the age of onset or disease duration significantly different between cases with SGP and those without SGP. In the PD patients, the UPDRS motor score differed significantly between groups (p = 0.01) with the PD/SGP patients having greater motor deficit than those without SGP. Conclusion: Although a common feature of PSP, SGP is not diagnostic for this condition and can be associated with other neurodegenerative causes of parkinsonism including PD. Highlights: Supranuclear gaze palsy (SGP) was studied in patients with autopsy-proven diagnoses. Most (9/14) but not all progressive supranuclear palsy (PSP) patients developed SGP. The clinical finding of SGP was not specific for a pathological diagnosis of PSP.